Firm survival and financial development: Evidence from a panel of emerging Asian economies - Tsoukas, Serafeim (Journal of Banking & Finance, 2011)
Using a panel of five Asian economies – Indonesia, Korea, Malaysia, Singapore and Thailand – over the period 1995–2007 we analyze the links between firm survival and financial development. We find that traditionally used measures of financial development play an important role in influencing firm survival. When stock markets become larger or more liquid firms’ survival chances improve. On the contrary, we show that higher levels of financial intermediation can increase firm failures. We also find that the beneficial effects of stock market development are more pronounced during the later years of our sample, while the adverse effects of bank intermediation have declined over time. Finally, large firms are more likely to benefit from developments in financial markets compared to small firms.